STRATEGI NEGARA-NEGARA G20 DALAM MENGANTISIPASI ANCAMAN KRISIS EKONOMI GLOBAL DI INDONESIA - Habibah Shobri; Anwar Syarif; Wirda Hediyati; Boy Ridho Hamgara; Purnama Ramadani Silalahi (Universitas Maritim AMNI Semarang, 2022)
The purpose of this research is to find out the strategies of the G20 countries in anticipating the threat of the global crisis in Indonesia. This study uses qualitative methods with a descriptive approach to be able to describe in depth. The G-20 believes that a solution to the economic crisis requires continuous global cooperation. Through this collaboration, the best ways to resolve the crisis are formulated, both what must be done by each member country of the G-20 and what must be done by and through international financial institutions. In addition, being in the G-20 provides an opportunity for Indonesia to take a closer look at how developed countries make policies and then implement them in Indonesia if deemed good and appropriate. Each country must pursue a number of policies in an effort to respond to the crisis through fiscal stimulus, stimulate recovery of economic growth again in the crisis era, and then strive for economic stability that is resistant to similar crises in the future through strengthening the domestic financial sector.